Dediščina v akciji Poti in načini vključevanja mladih v ohranjanje in interpretacijo dediščine - Fakin Bajec, Jasna (ZRC SAZU, Založba ZRC, 2021)
Stories, memories, relationships, traditional skills, dialects, and other tangible and intangible elements of cultural heritage provide opportunities and ways that can lead to compassionate, quality, authentic, and sustainable living in the present and in the future. The preservation and interpretation of unique cultural and natural artefacts from the past is not only in the hands of professionals from heritage institutions and research centres, but also in the hands of civil society of which children and youth are its integral part. Local people have become important participants in co-creating heritage, yet young people are still often not understood as equal bearers of culture or co-creators of heritage. How should we act to make youth's bold ideas heard and realised in heritage projects and activities? The handbook ('Heritage in action: Ways and opportunities of integrating heritage practices into educational programs') presents approaches, methods, techniques, and examples of good practice that can address children and young people to actively participate in the exploration and interpretation of the past and (re)creation of cultural heritage in their local community. It is intended for the educators in kindergartens, schools, universities, youth centers, and local associations who want to encourage the younger generations to a deeper understanding of their ancestors' lives.